EVALUATION OF WATER QUALITY IN ANIMAL FEED FACTORY ENVIRONMENT BASED ON PLANKTON AND BENTHOS BIOINDICATORS - Feni Yulinda; Tugiyono; Agus Setiawan; Elly Lestari Rustiati (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Water is a source of life that plays an important role for all living things. Rivers are one of the water sources that are vulnerable to pollution. This study aimed to evaluate the water quality of the Way Napal river based on the diversity of plankton and benthos. The research was conducted from November 2020 to March 2021. Sampling and analysis were performed by field technicians from the SEAMEO BIOTROP Environmental Laboratory. Plankton diversity was calculated using the Shannon Weaver diversity index. The results showed that the phytoplankton diversity index at AP-1, AP-2, and AP-3 locations ranged between 2,080-2,278 these values had moderate biota stability and were included in the uncontaminated category. The zooplankton diversity index at the AP-1 location has a value of 1,119 with moderate biota stability and is included in the moderate category, while at the AP-2 and AP-3 locations it has a value of 0.925-0.995 with unstable biota diversity and is included in the highly polluted category. The Benthos diversity index ranges from 1.343 - 1.772 with moderate biota stability and is included in the moderately polluted category.